2010
DOI: 10.3109/17453671003717807
|View full text |Cite
|
Sign up to set email alerts
|

Intracapsular pressure and interleukin-1β cytokine in hips with acetabular dysplasia

Abstract: Background and purpose Several studies have demonstrated an increased intracapsular pressure in several hip disorders such as septic arthritis, synovitis, and trauma. We therefore measured the intracapsular pressure in different positions in early dysplasic hips and its relation to the concentration of interleukin-1β (IL-1β), the volume of joint fluid, and the clinical and radiographic findings before a periacetabular osteotomy.Methods 12 female patients (12 hips, mean age 35 (18–52)) with hip dysplasia were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Xie et al . reported that the mean concentration of IL-1β in synovial fluid from early osteoarthritis in dysplastic hips was 55 (SD 12), ranging from 24 to 74 pg/mL [26]. Attur et al .…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al . reported that the mean concentration of IL-1β in synovial fluid from early osteoarthritis in dysplastic hips was 55 (SD 12), ranging from 24 to 74 pg/mL [26]. Attur et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few reports concerning cytokine levels in the hip joint. Although hip joint fluid IL-1b levels with acetabular dysplasia have been measured, the samples were collected after injection of 10 ml of saline inside the joint capsule [15]. Therefore they did not have an accurate cytokine level.…”
Section: Discussionmentioning
confidence: 99%
“…Thus inflammatory cytokines have been proposed to play a role in joint destruction in hip disease. Cytokines have been reported in the synovial fluid of diseased knees [6,7]; however, there have been few studies concerning the synovial joint fluid cytokine levels of diseased hips [15,16]. No study has evaluated the relationship between the severity of hip joint destruction and hip joint synovial fluid cytokine levels.…”
Section: Introductionmentioning
confidence: 99%
“…And the resulting insu cient blood supply to the femoral head and impaired venous return can, in turn, affect the repair of ONFH. Similarly, some studies demonstrate that less acetabular coverage can increase intracapsular pressure, and excessive weight bearing suffered by the hip joint can contribute to the development of ONFH [23][24][25][26]. Junfeng Zeng et al [27] nd that less acetabular coverage may be associated with the development of ONFH in East Asian population, which is also a factor affecting the repair of ONFH.…”
Section: Discussionmentioning
confidence: 99%